Benny & Joon [videorecording (Blu-Ray)] - Arnold, Susan; Roth, Donna Arkoff; Berman, Barry, 1957-; Chechik, Jeremiah; Depp, Johnny; Masterson, Mary Stuart, 1966-; Quinn, Aidan; Moore, Julianne; Platt, Oliver; Pounder, C. C. H.; Hedaya, Dan; Grifasi, Joe; et al. (MGM Home Entertainment, 2001)
A mentally ill young woman who lives with her older brother finds her love in an eccentric young man who models himself after Buster Keaton.